PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII MTS AL-KAUTSAR KARANG ANOM PADA MATERI PENCEMARAN LINGKUNGAN - SALOME RAJAGUKGUK (JURNAL ILMIAH MAKSITEK, 2019)
This study aims to determine the increase in motivation and student learning outcomes by applying the learning model of picture and picture type VII grade MTs Al-Kautsar Karang Anom 2019/2020 Academic Year. This research is a classroom action research (CAR) consisting of 2 cycles, and conducted two meetings. The subjects in this study were students of class VII D MTs Al-Kautsar Karang Anom, amounting to 22 students, while the object in this study was cooperative learning in the type of picture and picture, motivation and learning outcomes in environmental pollution material. The instruments used to obtain data are tests and questionnaires.The test is used to determine student learning outcomes and the questionnaire is used to determine student motivation after applying the cooperative learning model picture and picture type. Data analysis was performed to look for increased motivation and learning outcomes by using the type of picture and picture cooperative learning model conducted in cycle I and cycle II. From the results of the study it was found that the application of the cooperative learning model type picture and picture can increase the motivation and learning outcomes of Grade VII D MTs Al-Kautsar Karang Anom students on environmental pollution material.The increase in motivation that occurred in the first cycle was 40.91% to 81.81% in the second cycle with an increase of 40.90%. The increase in student learning outcomes in the first cycle was 45.45% to 81.81% in the second cycle with an increase of 36.36%. It was concluded that the application of the picture and picture type learning model can improve motivation and learning outcomes of Grade VII MTs Al-Kautsar Karang Anom students on environmental pollution material.